Crystal structures of sixteen phosphane chalcogenide complexes of gold(I) chloride, bromide and iodide - Daniel Upmann; Peter G. Jones; Dirk Bockfeld; Eliza Târcoveanu (Acta Crystallographica Section E: Crystallographic Communications, 2024)
The structures of 16 phosphane chalcogenide complexes of gold(I) halides, with the general formula R13-nR2nPEAuX (R1 = t-butyl; R2 = isopropyl; n = 0 to 3; E = S or Se; X = Cl, Br or I), are presented. The eight possible chlorido derivatives are: 1a, n = 3, E = S; 2a, n = 2, E = S; 3a, n = 1, E = S; 4a, n = 0, E = S; 5a, n = 3, E = Se; 6a, n = 2, E = Se; 7a, n = 1, E = Se; and 8a, n = 0, E = Se, and the corresponding bromido derivatives are 1b–8b in the same order. However, 2a and 2b were badly disordered and 8a was not obtained. The iodido derivatives are 2c, 6c and 7c (numbered as for the series a and b). All structures are solvent-free and all have Z′ = 1 except for 6b and 6c (Z′ = 2). All molecules show the expected linear geometry at gold and approximately tetrahedral angles P—E—Au. The presence of bulky ligands forces some short intramolecular contacts, in particular H...Au and H...E. The Au—E bond lengths have a slight but consistent tendency to be longer when trans to a softer X ligand, and vice versa. The five compounds 1a, 5a, 6a, 1b and 5b form an isotypic set, despite the different alkyl groups in 6a. Compounds 3a/3b, 4b/8b and 6b/6c form isotypic pairs. The crystal packing can be analysed in terms of various types of secondary interactions, of which the most frequent are `weak' hydrogen bonds from methine hydrogen atoms to the halogenido ligands. For the structure type 1a, H...X and H...E contacts combine to form a layer structure. For 3a/3b, the packing is almost featureless, but can be described in terms of a double-layer structure involving borderline H...Cl/Br and H...S contacts. In 4a and 4b/8b, which lack methine groups, Cmethyl—H...X contacts combine to form layer structures. In 7a/7b, short C—H...X interactions form chains of molecules that are further linked by association of short Au...Se contacts to form a layer structure. The packing of compound 6b/6c can conveniently be analysed for each independent molecule separately, because they occupy different regions of the cell. Molecule 1 forms chains in which the molecules are linked by a Cmethine...Au contact. The molecules 2 associate via a short Se...Se contact and a short H...X contact to form a layer structure. The packing of compound 2c can be described in terms of two short Cmethine—H...I contacts, which combine to form a corrugated ribbon structure. Compound 7c is the only compound in this paper to feature Au...Au contacts, which lead to twofold-symmetric dimers. Apart from this, the packing is almost featureless, consisting of layers with only translation symmetry except for two very borderline Au...H contacts.